SPECIFIC FEATURES OF WORD FORMATION IN LINGUISTICS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricate mechanisms that drive language evolution, focusing on word formation processes, structural peculiarities within the lexicon, and the fundamental roles played by root and affixal morphemes. Exploring diverse strategies such as derivation, compounding, blending, and conversion, the article elucidates how languages continuously adapt and innovate through these creative processes. It meticulously dissects the structural nuances of lexicons, highlighting the pivotal roles of roots and affixes in constructing and altering meanings within words. By elucidating the symbiotic relationship between these morphemes, the article underscores their significance as the foundational elements shaping linguistic expressions. This annotation serves as a valuable resource for linguists, language enthusiasts, and students seeking a comprehensive understanding of the dynamic nature of language and its intricate mechanisms of word formation.